Systematic Review: Pre-Stroke Use of Angiotensin Receptor Blockers and Stroke Outcomes - Ivana Purnama Dewi; Virandra B. Kusmanto; Kristin Purnama Dewi; Rizaldy Pinzon (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Background: Hypertension is the major risk factor and the most important modifiable risk factor for stroke. Angiotensin Receptor Blockers (ARB) are widely used in patient at high risk of cardiocerebrovascular events. The objective of this literature review was to determine the efficacy of pre-stroke use of ARB on stroke outcomes.Methods: Major medical databases (PubMed, MEDLINE, Clinical Key, Cochrane Library, EMBASE) were systematically searched using keyword: “hypertension”, “ARB”, “stroke”, and “outcome”. The search were limited to clinical trials published within the last 10 years, written in English, with full-text availability. We used GRADE Working Group to measure the quality of evidence.Results: Four clinical studies, three retrospective studies and one nationwide population-based cohort study met our inclusion criteria with total of 102.644 patients for analysis. The scientific quality of the studies varied from poor (1 study), moderate (1 study), and high quality (2 studies). Generally, the subjects of the studies were acute ischemic stroke patients. Three studies showed pre-stroke use of ARB were significantly associated with better stroke outcomes. Only one study found different result whereas pre-stroke use of ARB did not appear to affect stroke outcomes. Outcome of the studies was explored according to morbidity (severity and functional status upon discharge) and mortality (30-days mortality or in-hospital mortality). Several limitations were present, including non-random treatment assignment, retrospective study design, and lack of data for longitudinal medication exposure in observational studies.Conclusions: This systematic review shows evidence that there is possible benefit of pre-stroke ARB treatment in relation to better ischemic stroke outcomes. However, further studies with better research method quality are still needed. The efficacy of ARB treatment in relation to other type of stroke outcomes also needs to be furtherly examined.Keywords: ARB, pre-stroke, benefit, prognosis Makalah ini dipresentasikan dalam Poster Session 11th Scientific Meeting of Indonesian Society of Hypertension, 24-26 February 2017